Response of normal and colon cancer epithelial cells to TNF-family apoptotic inducers - Hofmanová, Jirina; Vaculová, Alena; Hyzd'alová, Martina; Kozubík, Alois (Oncology reports, 2008)
We compared the response of normal (FHC) and cancer (HT-29) human colon epithelial cells to the important apoptotic inducers TNF-alpha, anti-Fas antibody and TNF-related apoptosis inducing ligand (TRAIL). The two cell lines did not respond to TNF-alpha (15 ng/ml), expressed a limited sensitivity to anti-Fas antibody (200 ng/ml) and a different response to TRAIL (100 ng/ml). We studied apoptosis with regard to the changes at the receptor level (DR, DcR and FLIP) and at the level of mitochondria (Bid protein cleavage, Apo2.7 protein expression and caspase-9 activation). Two different approaches were used to sensitize the cells to TRAIL-induced apoptosis: inhibition of protein synthesis (cycloheximide, CHX) and inhibition of the pro-survival MEK/ERK pathway (U0126). While the two cell lines were markedly sensitized to all three TNF family members by CHX, a different degree of response (especially for TRAIL) was obtained when inhibition of the MEK/ERK pathway was achieved. TRAIL-induced apoptosis was significantly enhanced by U0126 co-treatment in the HT-29 cells, but not in the FHC cells. The most significant differences between the HT-29 and FHC cells co-treated with TRAIL and U0126 were demonstrated with regard to the involvement of the mitochondrial apoptotic pathway, suggesting its importance in the regulation of cell sensitivity to the TRAIL-induced apoptosis.
Keywords: proliferace buněk; apoptóza; buněčné linie; Caspases; Cell Line, Tumor; Tumor Necrosis Factor Decoy Receptors; Tumor Necrosis Factor-alpha; Apoptosis; TRAIL receptory; nádory tračníku; lidé; Proto-Oncogene Proteins c-bcl-2; Epithelial Cells; protoonkogenní proteiny c-bcl-2; Antibodies; Receptors, TNF-Related Apoptosis-Inducing Ligand; mitochondriální proteiny; Carcinoma; protein TRAIL; karcinom; Cell Line; Colonic Neoplasms; TNF decoy receptory; TNF-alfa; Cell Proliferation; Mitochondrial Proteins; kaspasy; TNF-Related Apoptosis-Inducing Ligand; epitelové buňky; protilátky; nádorové buněčné linie; Humans